Physics and chemistry of clouds - Lamb, Dennis, 1941- (Cambridge University Press, 2011)
"Clouds contribute to the environment in many ways. Clouds, through a variety of physical processes acting over many spatial scales, provide both liquid and solid forms of precipitation and nature's only significant source of fresh water. Under extreme circumstances, however, clouds and precipitation may not form at all, leading to prolonged droughts in some regions. At other times and places, too much rain or snow falls, giving rise to devastating floods or blizzards. Liquid rain drops bring usable water directly to the surface, while simultaneously carrying many trace chemicals out of the atmosphere and into the ecosystems of the Earth. Chemical wet deposition thereby supplies nutrients (and sometimes toxic compounds) to both terrestrial and aquatic lifeforms, as well as the weak acids responsible for the weathering of the Earth's crust. The solid forms of precipitation contribute in additional ways to the world as we know it. Snow, for instance, forms the winter snowpacks that dramatically affect the radiation balance and climate of high latitudes on a seasonal basis"--